Pengembangan Mahara Kalam dengan Media Arabic Scrabble Berbasis Kontekstual pada Siswa Kelas X Darul Iman - Fitri, Riani; Tarmizi , Ahmad; Nurani, Qoim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop and examine the effectiveness of a contextual-based Arabic Scrabble learning media in improving students’ Mahārah al-Kalām (Arabic speaking skills) at the tenth grade of Darul Iman Islamic Boarding School. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 24 students. Data were collected through observation, interviews, questionnaires, tests, and documentation, and analyzed using both qualitative and quantitative approaches, including expert validation and N-Gain analysis. The results indicated that the contextual-based Arabic Scrabble media achieved a very high validity level with an average percentage of 93%, indicating its feasibility for use in learning. The implementation of the media significantly increased students’ participation, motivation, and confidence in speaking Arabic. Furthermore, the effectiveness test showed a significant improvement in students’ speaking skills, as evidenced by the increase in pre-test and post-test scores. In conclusion, the contextual-based Arabic Scrabble media is proven to be an effective learning innovation that enhances students’ speaking skills in a more interactive, communicative, and meaningful way. This study is expected to serve as a reference for future development of innovative Arabic language learning media.